Cassini observations of ionospheric plasma in Saturn's magnetotail lobes. Issue 1 (25th January 2016) - Felici, M.; Arridge, C. S.; Coates, A. J.; Badman, S. V.; Dougherty, M. K.; Jackman, C. M.; Kurth, W. S.; Melin, H.; Mitchell, D. G.; Reisenfeld, D. B.; Sergis, N.
Abstract: Studies of Saturn's magnetosphere with the Cassini mission have established the importance of Enceladus as the dominant mass source for Saturn's magnetosphere. It is well known that the ionosphere is an important mass source at Earth during periods of intense geomagnetic activity, but lesser attention has been dedicated to study the ionospheric mass source at Saturn. In this paper we describe a case study of data from Saturn's magnetotail, when Cassini was located at ≃ 2200 h Saturn local time at 36  R S from Saturn. During several entries into the magnetotail lobe, tailward flowing cold electrons and a cold ion beam were observed directly adjacent to the plasma sheet and extending deeper into the lobe. The electrons and ions appear to be dispersed, dropping to lower energies with time. The composition of both the plasma sheet and lobe ions show very low fluxes (sometimes zero within measurement error) of water group ions. The magnetic field has a swept‐forward configuration which is atypical for this region, and the total magnetic field strength is larger than expected at this distance from the planet. Ultraviolet auroral observations show a dawn brightening, and upstream heliospheric models suggest that the magnetosphere is being compressed by a region of high solar wind ram pressure. We interpret this event as the observation of ionospheric outflow in Saturn's magnetotail. We estimate a number flux between (2.95 ± 0.43) × 10 9 and (1.43 ± 0.21) × 10 10  cm −2  s −1, 1 or about 2 orders of magnitude larger than suggested by steady state MHD models, with a mass source between 1.4 ×10 2 and 1.1 ×10 3  kg/s. After considering several configurations for the active atmospheric regions, we consider as most probable the main auroral oval, with associated mass source between 49.7 ±13.4 and 239.8 ±64.8 kg/s for an average auroral oval, and 10 ±4 and 49 ±23 kg/s for the specific auroral oval morphology found during this event. It is not clear how much of this mass is trapped within the magnetosphere and how much is lost to the solar wind. Key Points: Tailward observation of ionospheric plasma in the magnetotail lobe Evidence for simultaneous reconnection in the plasma sheet First observational estimate at Saturn of mass source rate from the ionosphere to the magnetotail